POLA HIDUP SEHAT IBU HAMIL DI KECAMATAN SUKAJADI KOTA PEKANBARU PROVINSI RIAU - ", Mardatillah; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The pattern of healthy living is a business person who wishes to be healthy by means of changing his lifestyle. A healthy lifestyle is a process in the survival pattern in order to achieve a healthy life. By implementing all of this is to have a healthy body, escape from disease, make the mind quiet, good physical health and spiritually. As for the pattern of healthy living pregnant woman is maintaining personal hygiene, choosing the right foods, doing health tests before pregnancy and experiencing pregnancy, do not perform intercourse with certain cases, lobbies for weight loss normal, always use clean water, use a clean latrines, hand washing with soap, do not consume alcohol, narcotics and other harmful substances, not smoking at home and pay attention to the work environment. Sampling technique used was Quota Sampling, the sample in this study was 75 pregnant women. The author uses descriptive quantitative methods with data collection in the form of observation, interview, questionnaire, documentation and library studies. Factors that can affect the behavior of healthy pregnant women is education, knowledge, experience, hereditary factors, environmental factors, and the trust factor. Based on the level of education, employment and relationships of the tribe or ethnicity with healthy living patterns of pregnant women toward healthy living patterns 11 pregnant women totaled 64 pregnant or 85.3% were already high, 9 pregnant women or 12.0% and two expectant mothers or 2.7% low in the running pattern of healthy living. So, the factors of education, employment and relationships of the tribe or ethnicity against healthy living patterns of pregnant women greatly influences because it needs knowledge, understanding or even experience in maintaining health for pregnant women during pregnancy take place, a smart and healthy mother will give birth to a child who is strong, healthy and smart too.Keywords : Pattern Of Healthy Living, Healthy Lifestyle, Factors That Influence Healthy Behaviors